Code-Switching and Code-Mixing Typologies and Functions in Negotiating Third-Space Hybridity in No Na’s “Rollerblade” - Wati Purnama Sari (Jurnal Ilmiah Multidisiplin, 2026)
In the era of globalization, language functions not only as a means of communication but also as a medium for negotiating identity and representing culture. This study examines the relationship between language use and cultural identity in No Na’s bilingual song “Rollerblade.” It aims to identify the types and communicative functions of code-switching based on Hoffmann’s framework, the types of code-mixing based on Muysken’s framework, and the ways in which these linguistic choices construct a cultural Third Space through Homi K. Bhabha’s postcolonial theory. This study employed a qualitative descriptive method. The data consisted of selected lyrical expressions containing Indonesian and English linguistic elements. The data were collected through purposive sampling and analyzed by classifying the forms of code-switching and code-mixing, identifying their communicative functions, and interpreting their relationship with Third Space dynamics. The findings reveal inter-sentential, intra-sentential, and tag code-switching, as well as insertion and congruent lexicalization in code-mixing. These linguistic strategies function to express group identity, provide interjections, clarify intentions, discuss particular topics, and emphasize statements. Their interaction reflects cultural mimicry, ambivalence, and subaltern agency. The findings indicate that No Na does not merely imitate Western popular culture but actively negotiates local and global identities by normalizing Indonesian cultural expressions within a global musical context. Thus, “Rollerblade” demonstrates how young people can participate in global culture while maintaining and reconstructing their local cultural identity.